ANÁLISE DA ESTRUTURA POROSA E DA RESISTÊNCIA À COMPRESSÃO DE CONCRETOS PARA UTILIZAÇÃO NA FABRICAÇÃO DE VIGOTAS DE LAJES PRÉ-MOLDADAS MISTAS PRODUZIDOS COM AGREGADO RECICLADO DE BLOCOS DE CONCRETO - Bardella, Paulo Sérgio; Saragosa, Gerson Cendes; Gaspar, William M. C. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The aim of this experimental work was to evaluate the compressive strength, capilar absorption and voids of concretes used in precast concrete with replacement of natural agregate for recycled agregate (50% and 100% replacement by mass). The concretes were produced with hight early strength Portland cement in the age of 7 and 28 days for compressive strength and 28 days for capilar absorption and voids. The results showed that the shape agregate and porcentage replacement influenced the durability and compressive strength of the concretes.